Marine eutrophication review - Hinga, Kenneth R.; Jeon, Heeseon; Lewis, Noelle F. (Silver Spring, MD U.S. Dept. of Commerce, 1995)
Contents: Part I: Quantifying the effcts of nitrogen enrichment on phytoplankton in coastal ecosystems. Part II: Bibliography with abstracts.
Keywords: Primary productivity(Biology); Coastal ecology; Marine phytoplankton; Marine euthrophication; Marine eutrophication